A Simple and Rapid Single Kernel Screening Method to Estimate Amylose Content in Rice Grains. Issue 6 (1st April 2013) - Agasimani, Somanath; Selvakumar, G.; Joel, A. John; Ganesh Ram, Sundaram
ABSTRACT: Introduction: In rice breeding programmes large number of grain samples are routinely analysed for amylose content (AC) through a tedious spectrophotometric method that also involves high reagent costs. Objective: Here, we propose a rapid and economic screening technique for assessment of AC based on the amylose–iodine complex formation in the cut grains of rice, which we refer to as the cut grain dip (CGD) method. Methods: The CGD method involves cutting the rice kernels in the middle with a pair of scissors and dipping the cut end in an optimised iodide:iodine (KI‐I) solution termed the rapid amylose detection solution (RADS). Results: It was found that the time taken for deep blue colouration by the cut end of the grains after dipping in RADS was proportional to the AC. The CGD method was further validated in a large set of rice mutants with varied AC. Conclusion: The proposed method can be used to screen samples for AC rapidly, with a single rice caryopsis, without any costly equipment and can be especially suitable for screening of mutants and segregants with altered AC in large breeding populations. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The Presently used standard protocols for the estimation of Amylose content (AC) are laborious and costly. A rapid screening protocol based on the amylose‐iodine complex which uses time duration for colouration of the cut grain portion has been developed and standardized. Perfect linear relationship between the time taken for colouration by the cut grain dip (CGD) method and the AC values estimated through routine spectrophotometric method validated the efficiency of this method.